Izin Pemanfaatan Hutan Negara Untuk Pertambangan Dalam Era Otonomi Daerah - Josef M Monteiro (Jurnal Hukum PRO JUSTITIA, 2006)
Izin Pemanfaatan Hutan Negara Untuk Pertambangan Dalam Era Otonomi Daerah